2019
DOI: 10.1108/jmd-11-2018-0327
|View full text |Cite
|
Sign up to set email alerts
|

Do social networking platforms promote service quality and purchase intention of customers of service-providing organizations?

Abstract: Purpose Customers are interested in finding service recommendations, reviews and word of mouth using social networking platforms. These service reviews are useful for enhancing service quality, level of information and engagement, and purchase intention of customers. The purpose of this paper is to uncover which social networking platform is more useful for the exchange of service reviews and how organizations are improving purchase intention as well as service quality in the light of customer’s reviews/experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 95 publications
2
26
0
4
Order By: Relevance
“…Also, it has been found that confidence in the experts' brand‐related content editing and sharing skills and their ability to effectively convey a message (e.g., language experts) may positively enhance brand engagement among SMUs. A recent study also verified that those individuals who have relevant industry experience may be considered better influencers on social media due to their personal experience or expertise (Naeem, 2019a). However, another study suggested that if consumers have personal expertise, but they are unknown in virtual communities, then they are unable to add social influence to shared UGC (Zhou & Duan, 2015).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Also, it has been found that confidence in the experts' brand‐related content editing and sharing skills and their ability to effectively convey a message (e.g., language experts) may positively enhance brand engagement among SMUs. A recent study also verified that those individuals who have relevant industry experience may be considered better influencers on social media due to their personal experience or expertise (Naeem, 2019a). However, another study suggested that if consumers have personal expertise, but they are unknown in virtual communities, then they are unable to add social influence to shared UGC (Zhou & Duan, 2015).…”
Section: Discussionmentioning
confidence: 83%
“…The second motivational factor is sharing experience. The existing literature has offered scattered evidence regarding why SMUs share their experiences (Kaur, Dhir, Rajala, & Dwivedi, 2018; Naeem, 2019a; Verhagen, Nauta, & Feldberg, 2013; Yao, 2014), especially in relation to fashion brands. These studies are limited to offering information about positive and negative emotions as the main reasons to share personal experiences related to common interests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is becoming common practice among organizations to adopt and exploit the properties and functionalities of social media. Effective and well-organized marketing activities on social media sites enable businesses to improve branding, CRM, research and sales promotion (Alves, Fernandes, and Raposo, 2016;Ashley and Tuten 2015;Naeem, 2019;Olanrewaju, Hossain, Whiteside, and Mercieca, 2020). With 3.48 billion users, social media represent a huge platform for businesses to promote products, services and access potential customers in the global audience (Olanrewaju et al, 2020;Sawicki, 2016).…”
Section: Introductionmentioning
confidence: 99%